2004
DOI: 10.1093/jn/134.1.104
|View full text |Cite
|
Sign up to set email alerts
|

The Time of Day of Food Intake Influences Overall Intake in Humans

Abstract: Circadian and diurnal rhythms affect food intake, and earlier research has suggested that meal sizes increase, whereas the after-meal intervals and satiety ratios decrease over the day. We hypothesized that the time of day of food intake would be related to total intake such that intake early in the day would tend to reduce overall intake, whereas intake later in the day would tend to increase intake over the entire day. The intakes of 375 male and 492 female free-living individuals, previously obtained via 7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
232
3
12

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(272 citation statements)
references
References 46 publications
25
232
3
12
Order By: Relevance
“…In previous studies [14] it was established that the higher the proportion of total food intake ingested in the morning the lower the daily intake, whereas the higher the proportion of total intake ingested in the late evening the higher the daily intake. These results suggest that intake during the morning is associated with lower intake throughout the day, whereas intake late at night is associated with higher levels of overall daily intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies [14] it was established that the higher the proportion of total food intake ingested in the morning the lower the daily intake, whereas the higher the proportion of total intake ingested in the late evening the higher the daily intake. These results suggest that intake during the morning is associated with lower intake throughout the day, whereas intake late at night is associated with higher levels of overall daily intake.…”
Section: Discussionmentioning
confidence: 99%
“…There are substantial and important changes in ingestive behavior that occur over the course of the day, but little is known regarding how the timing of nutrient ingestion impacts body weight. By analyzing 7-day diet diaries of 867 free-living individuals using epidemiological studies, De Castro suggested that 150% of energy is commonly ingested in the evening meals compared to morning meals [14]. As the calories of the meal increases during the day, the time before eating again decreases because food intake in the morning is particularly satiating, whereas food intake late at night is not satiating and can lead to greater overall energy intake [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…O horário das refeições pode ser relacionado com a ingestão total durante o dia. Os resultados desses estudos sugerem que ingerir um valor calórico maior pela manhã (ou primeira parte do dia) pode resultar em uma diminuição da ingestão total durante o dia, enquanto a ingestão de uma grande quantidade energética à noite pode resultar em um aumento do total da ingestão 43 .…”
Section: Ritmo Circadiano Alimentarunclassified
“…A recent study of 867 healthy adults (36.3-yearold, BMI 24.5 on average) who filled out 7 day diet diaries established that the proportion of daily intake ingested in the morning correlates negatively with total daily energy intake, while the proportion ingested late in the day correlates positively with overall energy intake (51). In other words, people who eat early eat less, while people who eat late eat more.…”
Section: Circadian Distribution Of Intakementioning
confidence: 99%